2023
DOI: 10.1111/jhn.13186
|View full text |Cite
|
Sign up to set email alerts
|

Is meal order timing and flexibility key to improving patient satisfaction with hospital foodservice?

Abstract: AimThe aim of this study was to retrospectively evaluate and compare patient foodservice (FS) satisfaction using a validated tool and consistent methodology in an acute health service for four different FS models as the organisation transitioned through traditional model (TM), choice at point of service (CaPOS), bedside menu ordering systems (BMOS) and room service (RS) from 2013 to 2016.MethodsPatient satisfaction data were collected using the Acute Care Hospital Foodservice Patient Satisfaction Questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…mix flexibility) that provide value to customers (Zhang et al, 2003). Therefore, healthcare services should emphasize the importance of quick responses to meet patient satisfaction (Barsha et al, 2023;Khuntia et al, 2022). Zhang et al (2003) support this argument as they found that flexibility has significant, positive and direct impacts on customer satisfaction.…”
Section: Quality and Satisfactionmentioning
confidence: 98%
“…mix flexibility) that provide value to customers (Zhang et al, 2003). Therefore, healthcare services should emphasize the importance of quick responses to meet patient satisfaction (Barsha et al, 2023;Khuntia et al, 2022). Zhang et al (2003) support this argument as they found that flexibility has significant, positive and direct impacts on customer satisfaction.…”
Section: Quality and Satisfactionmentioning
confidence: 98%